MAINSTREAMING SPORTS IN PESANTREN THROUGH A SPORT-BASED EMPOWERMENT APPROACH AND INSTITUTIONAL LEGAL COMPLIANCE - Husna, Faiqatul; Mukhlas, Umlina; Yunus, Nur Rohim (Indonesia Sport Journal, 2025)
This article examines the mainstreaming of sports in pesantren through a Sport-Based Empowerment (SBE) approach combined with institutional legal compliance as the foundation for sustainable implementation. Given that traditional pesantrens have long focused on religious studies and moral formation—resulting in insufficiently structured physical education—this study highlights the need to integrate sports into the holistic education of santri. Sports are positioned not merely as physical activity, but also as a medium for shaping Islamic character, leadership, cooperation, and mental resilience, in alignment with spiritual values such as discipline, brotherhood, and social responsibility. The study employs a qualitative method based on library research to analyze literature on sports empowerment, Islamic pedagogy, and educational regulations, including Law Number 18 of 2019 on Pesantren and standards for santri protection. The findings indicate that the role of sports in pesantren remains marginal, influenced by academic–religious traditions and limited facilities, yet holds significant potential if integrated into curricula and pesantren activities. The legal framework is shown to be a determining factor in ensuring that sports implementation complies with safety standards, governance requirements, and the rights of santri. The developed SBE model emphasizes the synergy between empowering santri through physical activities and legal compliance, thereby positioning sports as a means to improve health, reduce physical and mental disparities, and strengthen the institutional image and competitiveness of pesantren.